Inovasi Dosen Pendidikan Agama Islam dan Penggunaan TIK di Perguruan Tinggi - Al Qomari, Irkhas M. Nur (Lembaga Yasin AlSys, 2023)
This paper uses a theoretical approach to the conceptual study of educational innovation in the field of Higher Education and the use of Information and Communication Technology, as a fundamental support to achieve it. It is intended to present the idea of how the University is a producer of knowledge in a new culture and paradigm in which ICT generates a process of continuous transformation and improvement. Similarly, some educational technologies such as mobile phones and other mobile devices are in the classroom and can be a key element for learning. You should know what to do with them. That's the challenge that seats teachers around innovation. Special interest in technological innovations is manifested as the prerogative of relevance in the digital age. There is a certain consensus within the scientific community that is consulted, when understanding the educational innovations associated with the technologies of the digital age. It is important to value innovation as a procedural category that defines incremental or radical transformations to overcome, complement or enhance an object, process or phenomenon, which can be social, cultural, technical, productive, economic or environmental.